PENGARUH BUDAYA SEKOLAH TERHADAP PEMBENTUKAN KARAKTER SISWA DI MI AL-MA’ARIF 01 KABUPATEN SORONG - Oki Sandra Agnesa; Qaromah Dina Fitriana (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2020)
The aims of this study are: 1) to find out what cultural values ​​are developing in MI Al-Ma'arif 1 Sorong Regency, 2) to find out the characteristics of character cultural values ​​that develop in MI Al-Ma'arif 1 Sorong Regency, and 3) knowing the pattern of character culture education that has been applied. This type of research is descriptive quantitative research. The research subjects were students of MI Al-Ma'arif 01 Sorong Regency. Data collection techniques through interviews and questionnaires are used as supporting data in analyzing student character. The data analysis technique used the percentage technique. A series of values, norms, traditions, and habits are set by the school as a guide for school members in thinking, acting, and acting. The results of this study indicate that there are several customary activities implemented at the school, including the culture of greeting, praying sunnah dhuha, reading the Qur'an, praying before and after studying and paying infaq every Friday.